1933
DOI: 10.1097/00005053-193310000-00051
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Activity of the Spinal Cord

Abstract: and it is to be hoped that every one interested in the subject of reflex action will read this book.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1933
1933
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The eye performs several functions in which an inhibitory process should be useful [cf. Graham and Granit, 1931] Liddell and Sherrington, 1932] the physiology of the synaptic reactions has now been developed to a point when real significance may be derived from the fact that such reactions are present in the retina. A case in point is the question of area stimulated.…”
Section: Summarizing Conclusionmentioning
confidence: 99%
“…The eye performs several functions in which an inhibitory process should be useful [cf. Graham and Granit, 1931] Liddell and Sherrington, 1932] the physiology of the synaptic reactions has now been developed to a point when real significance may be derived from the fact that such reactions are present in the retina. A case in point is the question of area stimulated.…”
Section: Summarizing Conclusionmentioning
confidence: 99%
“…He began studying activity in motor axons with Sir Charles Sherrington (1857Sherrington ( -1952 at the University of Oxford, GBR by means of extracellular recording techniques (Creed et al, 1932). This work led to many key insights into the function of these neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers (Creed et al, 1932;Hart, 1971) observed only that intravenous injection of strychnine, a glycine receptor antagonist (Goodman-Gilman et al, 1991), "facilitated" scratching, flexion withdrawal, and various other reflex movements in low-spinal mammals. In the present study, we investigated the role of glycinergic inhibition in the generation and coordination of fictive rostral scratch motor patterns.…”
mentioning
confidence: 98%